Использование рефлексивных моделей Лефевра при создании интеллектуальных агентов в системах виртуальной реальности - Добронравин, Ю.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
Development of intellectual agents for virtual reality system is a very complex and laborious process. Modern virtual reality features complex simulation of some parts of the real world. This paper describes possibilities of using psychological models Vladimir Lefebvre to achieve more deep level of interaction with user within the system.